EFEKTIFITAS KEBIJAKAN ANTI-SLAPP DI INDONESIA UNTUK MENCEGAH KRIMINALISASI PERAN SERTA MASYARAKAT DALAM PERLINDUNGAN DAN PENGELOLAHAN LINGKUNGAN HIDUP YANG BAIK DAN SEHAT - Maharani, Farhanas; Sari, Indah (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
This study examines the effectiveness of anti-SLAPP policies in Indonesia in preventing the criminalization of community participation in protecting and managing a good and healthy environment. This study uses a normative legal method with a statutory, conceptual, and case approach. The main focus of the study is Article 66 of Law No. 32/2009 which is strengthened by the provisions of Law No. 6/2023 concerning Job Creation, which aims to protect the community and environmental human rights activists from criminalization. The results of the study show that although Article 66 of Law No. 32/2009 has the intention to protect the community, its implementation has not been fully effective. The lengthy legal process, high costs, and difficulties in proof hinder the effectiveness of this policy in preventing the SLAPP phenomenon. In addition, there is a lack of integration between law enforcement agencies and an unclear definition of obstructive acts. The government has a crucial role in formulating more comprehensive and proactive policies, ensuring stronger legal protection for community and environmental rights. Therefore, a more holistic policy is needed, which supports the protection of human rights and the environment, and is integrated with the existing legal system to optimize protection for activists and communities involved in the struggle for environmental rights.